1995
DOI: 10.1159/000168892
|View full text |Cite
|
Sign up to set email alerts
|

Coadministration of Ketoconazole to Cyclosporin-Treated Kidney Transplant Recipients: A Prospective Randomized Study

Abstract: In this work, 100 living related donor kidney transplant recipients under cyclosporin (CsA) therapy were randomly distributed to two groups. Group 1 were administered ketoconazole, with group 2 serving as the control. Ketoconazole was given orally, 100 mg/day, while the dose of CsA was adjusted for a CsA whole blood trough level of 100-150 ng/ml. Patients and controls were assessed regularly in an outpatient clinic for 12 months and compared statistically for CsA dose, graft and liver functions, cholesterol, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
26
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 13 publications
6
26
0
Order By: Relevance
“…Ketoconazole has been used in recent heart and kidney transplant studies. A cost-sparing effect was obtained by reducing the cyclosporin dosage required and because of its ef®cacy in preventing fungal infections and achieving a lower rejection rate [60,61]. However, care should be exercised not only because of drug interactions with azoles, but also because primary or secondary resistance to the antifungal drugs used may occasionally develop [62,63].…”
Section: Prophylaxis Of Fungal Infectionsmentioning
confidence: 99%
“…Ketoconazole has been used in recent heart and kidney transplant studies. A cost-sparing effect was obtained by reducing the cyclosporin dosage required and because of its ef®cacy in preventing fungal infections and achieving a lower rejection rate [60,61]. However, care should be exercised not only because of drug interactions with azoles, but also because primary or secondary resistance to the antifungal drugs used may occasionally develop [62,63].…”
Section: Prophylaxis Of Fungal Infectionsmentioning
confidence: 99%
“…We previously reported that co-administration of keto results in more stable graft function in kidney transplant recipients [6, 8]. Keogh et al [5] noticed that there was a reduction in the rejection rate (despite similar doses of azathioprine, prednisolone, and antithymocyteglobulin) in ketoconazole-treated cardiac transplant recipients.…”
Section: Discussionmentioning
confidence: 99%
“…Inrenal and cardiactransplantssome drugs, particularly ketoconazole and diltiazem, have been given purposefully with CsA in an attempt to markedly reduce the dose and therefore the cost of CsA [4,5,6]. Concurrent administration of ketoconazole and CsA permits a reduction in the CsA dosage of approximately 80%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After 1 year of follow-up, it was concluded that addition of ketoconazole to cyclosporine not only saved costs but also had a favorable effect on graft function, chronic cyclosporine nephrotoxicity, chronic rejection, and fungal skin infection. 10 After 54 months, dose reduction of cyclosporine was 72.9%. Moreover, metabolic consequences (lipid profile, bone mineral content, vitamin D blood levels) were not affected by long-term ketoconazole coadministration to cyc losporine.…”
Section: Prospective Randomized Trial Of Azathioprine Versus Cyclospomentioning
confidence: 99%